2019
DOI: 10.32637/orli.v49i1.271
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of preauricular based on plastic-reconstructive algorithm

Abstract: Background: Preauricular fistula is a congenital malformation of the six auditory hillocks during the development of auricle, when an imperfect fusion of the first arch tuberculum to other tuberculums occurred and generated a tract. It is characterized by a nodule or a dent located adjacent to the external ear. An infection will create a swollen area in front of ear auricles with pain and suppuration. Fistula extirpation should be carried out after the acute infection subsides. Purpose: To evaluate surgery tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…However the dye may not enter all the tiny branches so that precision is required during dissection to find the tiny, colorless ducts. 5 Huang et al conducted a study of operative management based on the severity of each case. The study concluded that patients with little or no inflammation (swelling, discharge, or erythema over the preauricular sinuses) could be surgically removed using a simple synectomy technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the dye may not enter all the tiny branches so that precision is required during dissection to find the tiny, colorless ducts. 5 Huang et al conducted a study of operative management based on the severity of each case. The study concluded that patients with little or no inflammation (swelling, discharge, or erythema over the preauricular sinuses) could be surgically removed using a simple synectomy technique.…”
Section: Discussionmentioning
confidence: 99%
“…The literature mentions that in Asia the incidence reaches 1-10%. 5 The right side appears to be more often involved and females more than males. 3 Usually asymptomatic, preauricular fistula patients frequently seek treatment due to infection.…”
Section: Introductionmentioning
confidence: 97%